Design of Automatic Parking Access System Based on Internet of Things (IoT) - Muhammad Hans Tobi (ITScience (Information Technology and Science), 2022)
Technology in this era is developing very rapidly and can help in daily activities. One of the roles of technology that can help daily activities can be fulfilled through smartphones. This study describes the design of a parking gate access system in a building using a QR Code as a parking gate access medium found in a smartphone application, as well as the use of the MQTT protocol which is applied to the network for data exchange processes, so that using this method can provide convenience for motorists. motorized vehicles to access the parking area using a smartphone. Based on the results of this research test, it was found that the QR Code reading works well at the distance between the smartphone and the camera, which is 15 cm to a maximum distance of 105 cm.